Study on microbial and physical changes in fish sauce during fermentation (Research in Agriculture Livestock and Fisheries, 2015)
The production of fermented fish sauce was replicated in the laboratory in order to study the microbiological and physical changes associated with the process. Fish sauce were produced by incubating mixtures of low valued small freshwater fish at different concentrations of sodium chloride (25% as Treatment-I, 30% as Treatment- II and 35% as Treatment-III) for 9 months of fermentation and 15 days of aging. Changes in bacterial composition and physical condition were observed. Due to effect of salt the bacterial population gradually changes and finally salt tolerant bacteria were survived and multiplied. The major bacterial groups identified in fish sauce were Bacillus, Micrococcus, Lactobacillus and Pseudomonas . Due to action of enzymes present in fish body and intestine the solid fish gradually converts in to liquid where salt acts a preservative to prevent the fish from spoilage. Finally the sensory analysis fish sauce was done through panel test. Considering the values of different parameters (salt content, test, colour and flavor) fish sauce produced with 25% salt (Treatment-I) was found to be of best quality.Res. Agric., Livest. Fish.2(2): 375-383, August 2015